To study the structure and thermodynamic properties of silicene materials when melting quickly by molecular dynamics simulation. (December 2020) - On, Vo Van
Abstract: This paper presents the results of the study of melting silicene by MD simulation with a sample of 6400 atoms. Silicene melting from 300K to 3500K with a rate of 1013K / s. Investigation of energy dependence on temperature shows a jump in the average total energy of molten Silicene at the temperature T = 2500K. The radial distribution function G(r), ring distribution, coordination number distribution, angle distribution, and distance distribution also studied, all show that the phase transition temperature of Silicene is about 2500K. At 3500K, the silicene structure is almost destroyed, but long-term bonds still account for a higher proportion than short-length bonds. The structure is almost homogeneous, symmetrical.